2003
DOI: 10.1073/pnas.0438057100
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization and nonrandom distribution of Kv1.3 potassium channels and CD3 molecules in the plasma membrane of human T lymphocytes

Abstract: Distribution and lateral organization of Kv1.3 potassium channels and CD3 molecules were studied by using electron microscopy, confocal laser scanning microscopy, and fluorescence resonance energy transfer. Immunogold labeling and electron microscopy showed that the distribution of FLAG epitope-tagged Kv1.3 channels (Kv1.3͞FLAG) significantly differs from the stochastic Poisson distribution in the plasma membrane of human T lymphoma cells. Confocal laser scanning microscopy images showed that Kv1.3͞FLAG channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
89
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 35 publications
4
89
0
Order By: Relevance
“…3 Top, red, Kv1.3͞FLAG labeled with anti-FLAG mAb followed by Alexa Fluor 546-RAMIG; green, MHC class I labeled with fluorescein-W6͞32 mAb; and blue, CD8 tagged by Alexa Fluor 647-MEM31 mAb). The distribution of Kv1.3 channels is similar to observations made on Jurkat cells by us (21) and by others (20). On the other hand, in CTLs conjugated with target cells, a rearrangement of Kv1.3͞FLAG was observed: in the majority of cases, ion channels were recruited into the CTL-target cell interface (Fig.…”
Section: Spatial Rearrangement Of Kv13͞flag In Ctls Engaged In Issupporting
confidence: 69%
See 4 more Smart Citations
“…3 Top, red, Kv1.3͞FLAG labeled with anti-FLAG mAb followed by Alexa Fluor 546-RAMIG; green, MHC class I labeled with fluorescein-W6͞32 mAb; and blue, CD8 tagged by Alexa Fluor 647-MEM31 mAb). The distribution of Kv1.3 channels is similar to observations made on Jurkat cells by us (21) and by others (20). On the other hand, in CTLs conjugated with target cells, a rearrangement of Kv1.3͞FLAG was observed: in the majority of cases, ion channels were recruited into the CTL-target cell interface (Fig.…”
Section: Spatial Rearrangement Of Kv13͞flag In Ctls Engaged In Issupporting
confidence: 69%
“…Our previous FRET studies on Jurkat cells indicated that Kv1.3͞FLAG molecules were in the molecular vicinity of CD3 (21). It was reported previously that CD3 molecules were also recruited into the IS formed between the CTL and the target cell (10).…”
Section: Spatial Rearrangement Of Kv13͞flag In Ctls Engaged In Ismentioning
confidence: 99%
See 3 more Smart Citations